Mercantilism and domestic industry in West-Central Nepal: Significance for Anthropological study of the community - Mikesell, Stephen L; Shrestha, Jamuna (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 1,297 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v2i0.1072 Occasional Papers in Sociology and Anthropology Vol.2 1990 p.77-89